A Plant Virus Disease Model with Periodic Environment and Pulse Roguing. Issue 4 (30th December 2015) - Gao, Shujing; Xia, Lijun; Liu, Yang; Xie, Dehui
Abstract : Regular roguing is an effective method to control plant virus diseases. In this paper, a compartmental mathematical model is established to represent the dynamics of plant disease in a periodic environment, including impulsive roguing control strategy. The basic reproductive number and its relation to the persistence of the disease is discussed via using next infection operation. Numerical simulations are performed to demonstrate the theoretical findings, and to illustrate the effect of control measures. Our results show that, (i) when the infection rate is high, it may be impossible to eradicate the disease by simply roguing the infectious plant, so how to effectively identify the latent plant is a key issue in disease control, (ii) increasing the replanting rate is bad for disease control, (iii) the published autonomous research model with continuous roguing may overestimate the infectious risk inherent to impulsive control.